Autoimmune bullous diseases during pregnancy: Solving common and uncommon issues - Aikaterini Patsatsi, MD, PhD; Branka Marinovic, PhD; Dedee Murrell, MA, BMBCh, FAAD, MD, FACD FRCP (Wolters Kluwer, 2019)
Autoimmune bullous diseases during pregnancy pose a therapeutic challenge for medical dermatologists. There are main concerns with regard to the regimen, dose, route of administration, and potential harm to the fetus. Many therapeutic options may be safe during pregnancy despite official classifications. Furthermore, there are always questions regarding management during the lactation period. Additionally, issues exist about male and female fertility and the time of discontinuation of certain medications before conception. In this article, we present an overview of the literature based on answers to these issues to solve common and uncommon management problems that arise about a spectrum of autoimmune bullous diseases before conception, as well as during pregnancy and the lactation period. Keywords: Pemphigus, pemphigoid, bullous, pregnancy, lactation fertility